Differences in union time, dash score and range of motion between giving bisphosphonate and without giving bisphosphonate of osteoporosis patients with distal radius fracture: a systematic review and meta-analysis - Dwiwahyonokusuma Dwiwahyonokusuma; Putu Astawa; I Wayan Suryanto Dusak; I Ketut Suyasa; Made Bramantya Karna (Intisari Sains Medis, 2021)
Background: Osteoporosis is a common health problem. Meanwhile, the incidence of distal radius fracture increases with osteoporosis. The standard modality for osteoporosis is a combination of pharmacological therapy, one example of which is the administration of bisphosphonates. There is some disagreement about bisphosphonates' effect on the treatment of distal radius fractures in osteoporosis patients. This study aims to conclude the effect of bisphosphonates for this condition on both functional and radiological outcomesMethods: A systematic search was carried out on the PUBMED database and Google Scholar on studies comparing the timing of bone fusion, Disability of Arm, Shoulder, And Hand (DASH) scores, and wrist Range of Motion (ROM) among distal radius fracture patients with or without additional bisphosphonate therapy. A prospective or retrospective cohort study and a randomized controlled trial were included in this study during 2000-2020. Inclusion and exclusion criteria were used for sample selection. Weight Mean Difference (WMD) was used to assess the statistical results in RevMan version 5.3 for Windows.Results: A search through the PUBMED and Google Scholar databases yielded 376 studies. Scanning titles and abstracts from studies that met the inclusion and exclusion criteria resulted in 6 articles. In total, there were 973 patients with distal radius fractures who received different treatment on bisphosphonate therapy. There was a significant difference in time to union with bisphosphonates (WMD=0.56; 95% CI=-0.94-2.06). Meanwhile, there was no significant difference in the assessment of DASH and ROM scores (WMD=0.27; 95% CI= -1.01-1.55).Conclusion Bisphosphonates provide a slower time to union in osteoporotic patients with distal radius fracture.